Effect of silt modification on the properties of magnesium phosphate cement - Wang, Haikuan; Li, Zhitang; Luo, Qiling; Long, Wujian (Frontiers in Materials, 2023)
Magnesium phosphate cement (MPC), as a new type of cementitious material, is difficult to be popularized in practical applications due to its short setting time, high cost, and poor water resistance. Dredging silt (DS) is a kind of hazardous waste, which may cause serious damage to the ecological environment if it is not disposed of properly. The treatment of DS and its reuse in building materials is an economical and environmentally friendly treatment method, which not only realizes the recycling of DS but also avoids secondary pollution. Using the treated DS as a mineral admixture for modified MPC not only recycles the DS but also improves the properties of MPC. In this paper, the effect of DS modification on the properties of MPC was investigated by setting time test, mechanical property test, water resistance test, and RCM test, and also compared with the modification effect of common mineral admixtures, such as fly ash (FA) and metakaolin (Mk), and finally analyzed by combining with SEM pictures. With the increase of the dosage of FA, Mk, and DS, the compressive strength of the modified MPC all showed the trend of increasing and then decreasing, and the optimal dosage was 5%, 10%, and 15%, respectively. At the optimum dosage, Mk and FA could improve the resistance of MPC to chloride erosion, but DS could not. The three kinds of admixtures could prolong the setting time of MPC, with DS having the best effect, followed by FA, and Mk having the smallest effect.All three admixtures could improve the water resistance of MPC, and the effect of improvement was Mk > DS > FA. The microstructure of the specimen was denser when the dosage of DS was low, and when the dosage was too much, the hydration reaction of MPC was affected, resulting in incomplete hydration and reduced hydration products. This research has significant guiding significance for the treatment of DS and the modification of MPC.